Evaluation of activation characteristics of a canine platelet concentrate produced by a commercial double centrifugation system - Tey, Nicole; Koenig, Amie; Hodges, Katie; Brainard, Benjamin M. (Frontiers in Veterinary Science, 2024)
Introduction In veterinary medicine there are few readily available products for platelet transfusion to patients with thrombocytopenia. Commercial tabletop platelet concentrating systems have recently become available to veterinarians, primarily directed towards uses associated with regenerative medicine. These systems could potentially be used to produce fresh concentrated platelets for use in transfusion medicine. This study evaluated the concentration, activation, and sterility of a double centrifugation platelet concentrate (PC) produced by a commercial benchtop system. Methods Ten healthy dogs were studied. Whole blood was collected and mixed with ACD-A in a 1:7.6 ratio of ACD-A to whole blood. 12 mL of this mixture was processed into PC via single centrifugation, while 60 mL of the anticoagulated whole blood was processed via a commercial double centrifugation system. Both types of PC were evaluated for platelet concentration, CD62P expression with and without thrombin stimulation, and for sterility. Results Mean platelet count in the double centrifuged PC was 863 ± 352 × 103/μL, with very low white blood cell contamination (median of 0.47 × 103 leukocyte/μL (range 0.15–2.18 × 103/μL)). The double-centrifuged PC had similar baseline activation characteristics (as determined by P-selectin expression) as the single centrifuge PC (0.76% vs. 0.72% unstimulated, 30.5% vs. 34.9% stimulated, p = 0.432). Discussion The benchtop PC system studied here did not cause activation of platelets during production and produced a sterile product that can be further investigated as a source of fresh platelet concentrates for transfusion purposes.